Analysis of Students' Errors in Solving HOTS Problems on Algebraic Materials Based on the Complexity Level of the Problem Based on Bloom's Theory - Muliana, Yulia; Abdillah, Abdillah; Mahsup, Mahsup; Syaharuddin, Syaharuddin; Ahmodu, Abdul-Lateef Olamide; Iddrisu, Mohammed Muniru (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2023)
Mathematics discusses a lot about various kinds of problems that contain numbers that are classified as Higher Order Thinking Skills (HOTS). Math HOTS questions require a high level of thinking to solve the problem. Based on Bloom's theory, HOTS consists of analyzing (C4), evaluating (C5), and creating (C6). This study aims to determine the level of student errors in solving HOTS questions based on Bloom's theory. This research uses mixed method research, which is a combination of qualitative and quantitative methods, where the stages of this research include instrument development, instrument validation, data collection, data analysis and interpretation. The sample of this study used 25 students of class VIII junior high school in Mataram City. Researchers gave 10 essay questions that had been validated by material experts to students as research instruments. The results showed that students' understanding in solving HOTS problems was still lacking. For the error rate, it was found that there were no students who could solve the creating (C6) section with a percentage of 100% error, analyzing (C4) section with a percentage of 60%, evaluating (C5) 24%, applying (C3) 16%, understanding (C2) 12%, and in the remembering (C1) section there were no students who made mistakes with a percentage of 0% error. The biggest error was found in the creating part (C6), where the most mistakes were made by women with an average score of 50.55.